2012
DOI: 10.1177/0091270010397050
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Inhibitor of p38 MAP Kinase Reduces Plasma Fibrinogen in Patients With Chronic Obstructive Pulmonary Disease

Abstract: The aims were to determine the effect of an oral inhibitor of the signaling mediator p38 mitogen-activated protein kinase (GW856553, losmapimod) on sputum neutrophils, pulmonary function, and blood biomarkers of inflammation in chronic obstructive pulmonary disease (COPD). Three hundred and two individuals with GOLD stage II COPD were randomized to oral losmapimod 7.5 mg twice daily, inhaled salmeterol/fluticasone propionate 50 µg/500 µg combination (SFC), or placebo in a 12-week, randomized, double-blind, dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 27 publications
2
75
1
1
Order By: Relevance
“…Another selective p38 MAPK inhibitor, losmapimod (29), showed to significantly inhibit either CSE-or acrolein-induced (Fig. 3, F and G).…”
Section: -E)mentioning
confidence: 96%
“…Another selective p38 MAPK inhibitor, losmapimod (29), showed to significantly inhibit either CSE-or acrolein-induced (Fig. 3, F and G).…”
Section: -E)mentioning
confidence: 96%
“…tolerance). Oral p38 mitogen-activated protein kinase inhibitors have small effects [158] or no effects [159], and inhaled drugs are in development. Other kinases targeted for COPD include Janus-activated kinase, phosphoinositide-3-kinase, and spleen tyrosine kinase, but no clinical studies have been reported.…”
Section: Novel Pharmacological Therapiesmentioning
confidence: 99%
“…Additionally, p38 MAPK acts post-transcriptionally by stabilising mRNAs, and promotes protein translation [7]. p38 MAPK inhibitors reduce cytokine production from alveolar macrophages [8][9][10][11] and are in clinical development for the treatment of COPD [12,13].…”
Section: Introductionmentioning
confidence: 99%